2019
DOI: 10.21203/rs.2.16094/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility and plasmid profiling of Vibrio spp. isolated from cultured groupers in Peninsular Malaysia

Abstract: Background: Numerous prevalence studies of Vibrio spp. infection in fish have been extensively reported worldwide, including Malaysia. Unfortunately, information on the prevalence of Vibrio spp. in groupers ( Epinephelus spp.) is limited. In this study, groupers obtained from nine farms located at different geographical regions in Malaysia were sampled for the presence of pathogenic Vibrio spp. and their susceptibility profiles against seven antibiotics. Results: Out of 270 grouper samples, 195 (72%) were dete… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Other studies from Iran, South‐East Asian countries and China reported prevalence values between 0% and 58.6%, with a slightly lower occurrence in fish than in crustacean (e.g. shrimps and prawns) (Elhadi et al., ; Yano et al., ; Gopal et al., ; Ji et al., ; Koralage et al., ; Raissy et al., ; Pan et al., ; Paydar and Thong, ; Tey et al., ; Wong et al., ; Tra et al., ; Amalina et al., ; Yan et al., ), while high detection rates were reported for fish from Mexico Gulf (37–51%) and for crabs from the Atlantic coast of USA (Tao et al., ; Baumeister et al., ; Rodgers et al., ). As for V. parahaemolyticus , according to a recent meta‐analysis of available studies, the prevalence of this species in seafood amounts to 48.3% (95% CI: 0.454–0.512) in crustaceans and to 51.0% (95% CI: 0.476–0.544) in fish and cephalopod (Odeyemi, ).…”
Section: Appendix a – Search Strategies And Outcome Of The Literature Searches Supporting The Hazard Identificationmentioning
confidence: 96%
“…Other studies from Iran, South‐East Asian countries and China reported prevalence values between 0% and 58.6%, with a slightly lower occurrence in fish than in crustacean (e.g. shrimps and prawns) (Elhadi et al., ; Yano et al., ; Gopal et al., ; Ji et al., ; Koralage et al., ; Raissy et al., ; Pan et al., ; Paydar and Thong, ; Tey et al., ; Wong et al., ; Tra et al., ; Amalina et al., ; Yan et al., ), while high detection rates were reported for fish from Mexico Gulf (37–51%) and for crabs from the Atlantic coast of USA (Tao et al., ; Baumeister et al., ; Rodgers et al., ). As for V. parahaemolyticus , according to a recent meta‐analysis of available studies, the prevalence of this species in seafood amounts to 48.3% (95% CI: 0.454–0.512) in crustaceans and to 51.0% (95% CI: 0.476–0.544) in fish and cephalopod (Odeyemi, ).…”
Section: Appendix a – Search Strategies And Outcome Of The Literature Searches Supporting The Hazard Identificationmentioning
confidence: 96%
“…as it resistant to at least two antibiotics. MAR index with value more than 0.2 indicate a 'highrisk' source of antibiotic contamination [20]. The location was in the urban area that affected by the residential area, industrial activities and aquaculture farm.…”
Section: Mar Index Analysismentioning
confidence: 99%